Competition in farm product markets: do long-run incentives trump short-run market power? - Crespi, John M.; Saitone, Tina L.; Sexton, Richard J. (My University, 2013)
This paper addresses buyer market power in farm product procurement markets. We argue that buyer power concerns are often overstated because traditional models of buyer market power are incapable of depicting the economic interactions that are fundamental to modern agricultural markets, where exchange is governed by stable contractual relationships among buyers and farmers. The exercise of short-run oligopsony power is inimical to the long-run interests of buyers in these settings because below-competitive returns will lead to the exodus of resources from producing the product. Policy proposals grounded in the presumed linkage between concentration, competition, and market power may well be misguided and detrimental to the objectives proponents seek to advance.
Competition in U.S. farm product markets: do long-run incentives trump short-run market power?
Keywords: Oligopsony power; Contracts; Agricultural markets; Vertical coordination